The adoption - Zidrou (Magnetic Press, 2020)
"When aging Gabriel's son and daughter adopts an orphaned girl from Peru, Gabriel doesn't know what to think of this foreign child who isn't of his own blood. Besides, he was barely much of a father to his own son...how is he going to take to being a grandfather? The story is made up of moments of sharing between the grandfather and the granddaughter, as well as various interactions around this dilemma with his wife, his lifelong friends, and his own son himself. But when surprise twists complicate matters, true feelings blossom and Life takes on a whole new palette"--Provided by publisher.